The Methode of Understanding Hadith on Shafi’i’s View on His Book “al-Risala” | منهج فهم السنة النبوية عند الامام الشافعي في كتابه ”الرسالة“ - Abdul Hakim Wahid (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2016)
This article discusses the methods Shafi'i in understanding hadith. Shafi'i fiqh is a character who is also an expert in Hadith, he was the person who first examines the contradictions in the hadith. In his book, al-Risalah. Syafii tried to explain the hadith with his opinions and methods. This study is the literature, This study describes a method Shafi'i in understanding hadith, approach to understanding of hadith.